2018
DOI: 10.1111/rda.13327
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids profile within peripheral blood and follicular fluid based on high‐performance liquid chromatography methods may explain differences in folliculogenesis between short‐term under/over‐fed treatments during luteal phase of Hu sheep

Abstract: The nutritional alteration of amino acids (AAs) profile in physiological fluid was poorly characterized in livestock. After oestrus synchronization, 24 ewes were randomly assigned to two groups based on the nutrient requirement recommended for maintenance (M): the feed-supplemented group (S, 1.5 × M, N = 12) and feed-restricted group (R, 0.5 × M, N = 12) on days 6-12 of their oestrous cycle, which occurred shortly before ovulation. The concentration of 30 AAs in peripheral blood (PB) and follicular fluid (FF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…Forde et al (2016) reported FF ornithine had a significant positive correlation with serum IGF1 and insulin, and a significant negative correlation with serum BHBA in heifers and lactating cows. This is consistent with Nie et al (2019), who reported that FF ornithine had a significant positive correlation with follicular insulin and glucose and a negative correlation with follicular NEFA concentrations in ewes fed restricted or supplemented diets. These effects were specific to ornithine and not the other amino acids measured in this study, with the exception of arginine which also had a positive correlation with FF glucose concentration (Nie et al 2018).…”
Section: Amino Acidssupporting
confidence: 92%
“…Forde et al (2016) reported FF ornithine had a significant positive correlation with serum IGF1 and insulin, and a significant negative correlation with serum BHBA in heifers and lactating cows. This is consistent with Nie et al (2019), who reported that FF ornithine had a significant positive correlation with follicular insulin and glucose and a negative correlation with follicular NEFA concentrations in ewes fed restricted or supplemented diets. These effects were specific to ornithine and not the other amino acids measured in this study, with the exception of arginine which also had a positive correlation with FF glucose concentration (Nie et al 2018).…”
Section: Amino Acidssupporting
confidence: 92%